A Mini-review on Childhood Gynecomastia - Jurayyan, Nasir A. M. Al (Current Practice in Medical Science Vol. 7, 2022)
Gynecomastia was reported to cause an imbalance between estrogen and androgen action or an increased estrogen to androgen ratio, due to increased estrogen production, decreased androgen production or both. Enlargement of the male breast tissue, known as gynecomastia, is a typical finding in boys during childhood. Although the majority of cases are benign and self-limiting, they could be an indication of a systemic disease or even drug-induced. Rarely, it may represent male breast cancer. Understanding its pathogenesis is crucial to distinguish a normal developmental variant from pathological cases. In conclusion, this review will highlight the pathophysiology, etiology, diagnosis and various medical and surgical therapies.